Repair of Ventricular Septal Defect in a Patient with Hemophilia A: Case Report - Sharma, Sona (Journal of College of Medical Sciences-Nepal, 2023)
Hemophilia is an X-linked recessive hemorrhagic disease that affects 1 in 10,000 males worldwide, in all ethnic groups; hemophilia A represents 80% of all cases. Congenital heart disease is the most commonly occurring birth defect; it is formed during the intrauterine period. The combination of these two disease is rather rare and requires the cardiosurgeon’s apprehensive attitude. Here, we present our experience in the surgical treatment of a boy of 1-year-old with Perimembranous Ventricular Septal Defect with Hemophilia A which was found in preoperative examination. He was successfully operated with cardiac pulmonary bypass on the background of factor VIII injection.